Variation of claim within the trial hearing: Can its validity still be denied? - Baldeón Bedón, Luis Jesús (2022)
The author considers that the validation of the modification of the claim within the trial hearing, based on the current circumstances, should be the subject of immediate evaluation among the national procedural authors. This is because the initial pleading stage is currently handled within the conduits of orality, which allow more easily identify the object of the claim with the material facts that have sustained it. For this reason, our labor procedural system no longer has, for more than ten years, a static or written model, where only the formulations between the parties were made in written form but now the interrelation is dynamic between the parties (virtual or face-to-face), through the respect for the counterparty’s right to defense.